2016
DOI: 10.19071/jmhe.2016.v2.2929
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Wound Healing Effect of Water Extract of Stereospernum kunthianum Stem-Bark

Abstract: The objective of the present study was to evaluate the in vivo wound healing effect of water extract of Stereospermum kunthianum cham. (SK)-bark. The plant is mainly used by the local people of Mayo-Danay, Cameron as wound healing agent. The healing activity was evaluated in rats using excision and incision wound on normal dexamethasone (DX)-delayed wound healing. Control animals received normal saline topically while other groups received DX (intramuscular [i.m.]), water extract orally or DX with the plant ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Several studies have shown that many biological activities of plant extracts are often linked to their polyphenol content. These are antioxidant [4], anti-inflammatory [5] anti-tumour [6] and healing [7] activities. They also have a stimulating action on immune system cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that many biological activities of plant extracts are often linked to their polyphenol content. These are antioxidant [4], anti-inflammatory [5] anti-tumour [6] and healing [7] activities. They also have a stimulating action on immune system cells.…”
Section: Introductionmentioning
confidence: 99%